2021
DOI: 10.1093/hmg/ddab359
|View full text |Cite
|
Sign up to set email alerts
|

Selective retinal ganglion cell loss and optic neuropathy in a humanized mouse model of familial dysautonomia

Abstract: Familial dysautonomia (FD) is an autosomal recessive neurodegenerative disease caused by a splicing mutation in the gene encoding Elongator complex protein 1 (ELP1, also known as IKBKAP). This mutation results in tissue-specific skipping of exon 20 with a corresponding reduction of ELP1 protein, predominantly in the central and peripheral nervous system. Although FD patients have a complex neurological phenotype caused by continuous depletion of sensory and autonomic neurons, progressive visual decline leading… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 10 publications
(21 citation statements)
references
References 64 publications
2
18
0
Order By: Relevance
“…5A). As previously reported 59 , the FD mice at three months of age did not yet show a significant loss in RGC (Fig. 5B).…”
Section: Resultssupporting
confidence: 88%
See 4 more Smart Citations
“…5A). As previously reported 59 , the FD mice at three months of age did not yet show a significant loss in RGC (Fig. 5B).…”
Section: Resultssupporting
confidence: 88%
“…Mice were maintained in the same treatment regime for the entire trial duration and were sacrificed at 6 months of age for tissue collection. Our previous studies in the FD mouse show that by 6 months of age the disease phenotype is evident and quantifiable 56,59 . We started the treatment at birth to maximize the therapeutic value, and a preliminary study that assessed ELP1 expression in transgenic pups after PTC258 treatment showed that this compound can pass from dams to pups through lactation and increase the functional ELP1 protein amounts in the pups (Supplementary Fig.…”
Section: Resultsmentioning
confidence: 90%
See 3 more Smart Citations